From Struggles to Success: Investigating the Impact of Early Learning Assessments on Students Performance and Motivation - Christopher T. Boyle; Nicole N. Hashemi (MDPI AG, 2023)
In this paper, we investigated the impact of an early learning assessment on students' motivation for improving their performance throughout the semester. An observation analysis was conducted on an entry level mechanical engineering course in which students are enrolled during their first semester of engineering work. This study analyzes the effect that a first exam, with an average below a passing grade, has on a student's outcome in the course. It was hypothesized that students were motivated to achieve their desired grade outcomes following an inadequate performance on the first exam. This was investigated by diving into the results of the course and referencing initial performance to the remaining exam and assessment outcomes. Students were placed into grade bands ranging between 0 and 100 in 20% increments. Their results were tracked, and it was shown that for the second mechanics exam, the averages increased by 43.333%, 35.35%, and 30.055% for the grade bands: 0 to 20, 20 to 40, and 40 to 60, respectively. The assessment grades also increased, with the remaining assessments being averaged to a score of 91.095%. The variables contributing to student performance came from both inside and outside the classroom. Learning communities, material differentiation, and student and professor adaptation all contributed to the rise in performance. It was concluded that the internal and external variables acted in combination with one another to increase student dedication to achieving success.